Respuesta :

[tex](2a^2+ab+2b)+(4a^2-3ab+9)\\\\=2a^2+ab+2b+4a^2-3ab+9\\\\=(2a^2+4a^2)+(ab-3ab)+2b+9\\\\=\boxed{6a^2-2ab+2b+9}[/tex]

Answer:

The sum is  [tex]6a^2-2ab+2b+9[/tex]

Step-by-step explanation:

Given two expression

[tex](2a^2 + ab + 2b)[/tex] and [tex](4a^2 − 3ab + 9)[/tex]

We have to find the sum of above two expression.

[tex](2a^2 + ab + 2b)+(4a^2 - 3ab + 9)[/tex]

Combining like terms we get

[tex](2a^2+4a^2)+(ab-3ab)+2b+9[/tex]

= [tex]6a^2-2ab+2b+9[/tex]

The sum is  [tex]6a^2-2ab+2b+9[/tex]